The Cysteine Protease MaOC1, a Prokaryotic Caspase Homolog, Cleaves the Antitoxin of a Type II Toxin-Antitoxin System - Klemenčič, Marina; Halužan Vasle, Ana; Dolinar, Marko (Frontiers in Microbiology, 2021)
The bloom-forming cyanobacterium Microcystis aeruginosa is known for its global distribution and for the production of toxic compounds. In the genome of M. aeruginosa PCC 7806, we discovered that the gene coding for MaOC1, a caspase homologue protease, is followed by a toxin-antitoxin module, flanked on each side by a direct repeat. We therefore investigated their possible interaction at the protein level. Our results suggest that this module belongs to the ParE/ParD-like superfamily of type II toxin-antitoxin systems. In solution, the antitoxin is predominantly alpha-helical and dimeric. When coexpressed with its cognate toxin and isolated from Escherichia coli, it forms a complex, as revealed by multi-angle light scattering and affinity purification. The active site of the toxin is restricted to the C-terminus of the molecule. Its truncation led to normal cell growth, while the wild-type form prevented bacterial growth in liquid medium. The orthocaspase MaOC1 was able to cleave the antitoxin so that it could no longer block the toxin activity. The most likely target of the protease was the C-terminus of the antitoxin with two sections of basic amino acid residues. E. coli cells in which MaOC1 was expressed simultaneously with the toxin-antitoxin pair were unable to grow. In contrast, no effect on cell growth was found when using a proteolytically inactive MaOC1 mutant. We thus present the first case of a cysteine protease that regulates the activity of a toxin-antitoxin module, since all currently known activating proteases are of the serine type.